ANALISIS RAGAM BELANJA UNIVERSITAS CAMBRIDGE: STRATEGI PENGADAAN DI PERGURUAN TINGGI KELAS DUNIA - Rofiq Setiawan; Suryono Suryono; Muhammad Munadi (STKIP Pesisir Selatan, 2026)
This study analyzes the spend variety at the University of Cambridge, one of the oldest and most prominent universities globally. Using a descriptive-qualitative approach with a case study method, this research examines financial reports, public contracts, and budget allocation documents from 2020-2025. The findings indicate that Cambridge implements a strategic procurement model combining collective purchasing consortia for strategic commodities with decentralized flexibility for specialized expenditures. This model achieves cost efficiencies of 19-24% in specific categories while generating a regional economic impact worth £1.61 billion in gross value added (GVA). The hybrid governance structure between central University and autonomous colleges proves effective in managing complex spending across nine main categories. This research contributes to higher education management literature by providing an analytical framework for spend variety adoption in developing countries. However, structural deficits require fundamental business model transformation beyond procurement efficiency alone